Effects of Wolbachia removal on microbial composition and diversity in Aedes albopictus: implication of using wAlbB for discriminating irradiation-based sterile and wild males - Paerhande Dilinuer; Ming Li; Datao Lin; Yu Wu; Zhongdao Wu; Xiaoying Zheng; Dongjing Zhang (Infectious Diseases of Poverty)
Abstract Background The sterile insect technique (SIT) requires distinguishing sterile from wild male mosquitoes to evaluate male qualities and maintain an appropriate release ratio for efficient population suppression. Current dye/powder marking methods have limitations and may affect SIT effectiveness, necessitating alternative discrimination strategies. Aedes albopictus naturally harbors two Wolbachia infections (wAlbA/wAlbB), which can be eliminated via tetracycline. Although Wolbachia removal minimally affect host fitness, its impact on microbiota remains unclear. Characterizing post-elimination microbial communities is the first step to identify novel endogenous biomarkers for SIT monitoring. Methods We analyzed the bacterial diversity and composition of two strains of wild-type GUA (Wolbachia-infected) and GT (Wolbachia-free) mosquitoes using the 16S rRNA V3-V4 region sequencing. qPCR was employed to confirm the relative abundance of four major bacterial genera, while PCR was used to validate selected biomarkers for distinguishing factory-reared sterile males from wild males. Kruskal-Wallis or Mann-Whitney test was used to analyze the comparable parameters between GUA and GT strains. Results Five-day-old GUA and GT females showed similar microbial diversity/composition, while young males shared diversity but differed in composition. The core microbiota in both strains consisted of Proteobacteria (64.27%), Firmicutes (16.09%), Actinobacteriota (11.22%), and Bacteroidota (4.96%). Asaia was dominant in both strains (GUA: 47.33%; GT: 32.69%), whereas Enterococcus increased in GT males with aging. Wolbachia was absent in GT mosquitoes, and Elizabethkingia was undetected in GUA males. qPCR further confirmed these trends. PCR analysis revealed that wAlbB exhibited higher stability in differentiating factory-reared GT males from their wild counterparts (96.7% infection in field males, n = 60) compared to wAlbA (61.7%, n = 60) or Enterococcus (65.8%, n = 120). The mark-release-recapture experiment further confirmed the detectability using wAlbB biomarker. Conclusions Without obvious fitness costs observed previously in the Ae. albopictus GT strain compared to GUA strain, the removal of Wolbachia significantly changes the microbial composition in male mosquitoes in this study. Wolbachia wAlbB is recommended as a reliable biomarker for distinguishing sterile males from wild males when using GT strain in SIT programs targeting Ae. albopictus. Graphical Abstract